Hadith Masyhur dalam Masyarakat Melayu: Takhrij dan Analisis - Dakir, Jawiah; Mohsin, Budah@Udah; Ibrahim;, Mazlan; Ahmad Shah, Faisal (Jurnal Usuluddin, 2008)
This article actually is a research project focussed on famous (mashhur)Hadith that had been spreaded and used among Malay Muslim society. Famous Hadith that had been collected will be examined to clarify its quality either as a sound (sahih) Hadith, weak (da`if) or fabricated (mawdu`)Hadith. The objective of this research is to collect famous Hadith, then to verify the status and quality of Hadith and reveal it to the society. This research has succeded in collecting famous Hadith from various sources such as general books, Jawi’s books, magazines, newspapers, Juma`at sermons, lectures such as Forum Perdana Hal Ehwal Islam, TV1 Malaysia and etc. The methods of Hadith scholars in evaluating and verifying Hadith has been used in determining the qualityof Hadith. This research is hopefully will come out with the collection of invalid Hadith that had been spreaded to the Muslim community therefore to alert and prevent them from using it.